Sistem Informasi Agen Perjalanan Pariwisata Di Sumatera Selatan Berbasis Web - Dewi Handayani; Suryayusra (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
This study aims to create a travel agent information system to facilitate the booking andpayment center for tours. The author here takes the place to conduct research in one of thecities in South Sumatra, namely Pagaralam City. The research method used is observation,interviews, and literature study. With this website, it is hoped that tourists can help, simplify,and speed up in finding and obtaining information about the location of tourist attractions inPagaralam City. Pagaralam City is one of the cities in South Sumatra Province which is famousfor its charming tourist attractions. Tourist destinations such as mountains, as well as varioustypes of waterfalls, artificial tourism, historical tourism, and religious tourism. The researchwas carried out in several tourist attractions in the city of Pagaralam. In this presentationabout tourism, it is easier for tourists to determine travel planning and easy to determine whichtour to visit in Pagaralam City, South Sumatra. But there are still many tourists who do notknow or there are still many tourists who are still confused in determining tourist attractions.which one to visit. In addition, travel agents in South Sumatra Province, especially Pagaralam City, can develop. Therefore, it is necessary to develop a website for this web-based tourismagent information system to support tourism in Pagaralam City and as a medium for travelagents in making tour packages. The development of this application consists of several stages,namely planning, design, coding, testing with the Extreme Programming method and systemtesting with the blackbox method. This website can be used to view, search, and find outinformation on tour packages and make it easier for tourists to see tour packages in PagaralamCity, South Sumatra.